Kebijakan Vaksinasi Covid-19 dalam Perspektif Konstitusi - Kasim, Aminuddin; Rahmat Bakri; Supriyadi; Purnamasari, Andi Intan; Rizal, Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2024)
The existence of Covid-19 in Indonesia has now had its status changed from pandemic to endemic. However, its existence still poses a serious threat to the general health of Indonesian citizens. Since 2019, the government still pays close attention to the existence of Covid-19, by implementing various policies to ensure health protection for the citizens as a Constitutional mandate. In the light of that, this research discusses how the concept of protecting the right to health is understood in the Constitution and whether the vaccination policy is in line with the Constitution. This research uses normative methods. This research concludes that, first, the concept of protecting the right to health in the Constitutional takes the form of understanding with a social-solidarity dimension which is based on the protection of human rights as part of human dignity in achieving public benefits. Second, the vaccination policy implemented by the government is in line with Constitutional values considering it includes protection of the right to health.Keywords: Constitution; Covid-19; Policy; Vaccination. AbstrakKeberadaan Covid-19 di Indonesia saat ini telah mengalami perubahan status dari pandemi menjadi endemi, akan tetapi keberadaannya masih memberikan ancaman yang serius bagi kesehatan warga negara Indonesia. Sejak Tahun 2019 hingga saat ini pemerintah masih memberikan perhatian terhadap keberadaan Covid-19, dengan melakukan berbagai kebijakan guna memastikan perlindungan Kesehatan bagi warga negara sebagai amanat konstitusi. Sehingga penelitian ini membahas bagaimanakah konsep perlindungan hak Kesehatan dalam paham konstitusi dan apakah kebijakan vaksinasi telah selaras dengan konstitusi. Penelitian ini menggunakan metode penelitian normatif. Penelitian ini berkesimpulan, yakni, pertama, konsep perlindungan hak Kesehatan dalam paham konstitusi bermatra sosial-solidaritas yang bertumpuh pada perlindungan hak asasi manusia sebagai bagian dari harkat kemanusiaan dalam mengapai kemaslahatan. Kedua: kebijakan vaksinasi yang dilakukan oleh pemerintah telah selaras dengan nilai–nilai konstitusi karena memuat perlindungan terhadap hak kesehatan.Kata Kunci: Covid-19; Kebijakan; Konstitusi; Vaksinasi